Knowledge, attitudes, perceptions, and practices regarding cutaneous larva migrans in deprived communities in Manaus, Brazil - Lesshafft, Hannah; Schuster, Angela; Reichert, Felix; Talhari, Sinesio; Ignatius, Ralf; Feldmeier, Hermann (The Journal of Infection in Developing Countries, 2011)
Introduction: Hookworm-related cutaneous larva migrans (HrCLM) is a neglected parasitic skin disease commonly found in resource-poor communities in tropical countries. It is acquired via skin contact with faeces of cats and dogs, and causes intense pruritus and significant morbidity. Methodology: We investigated knowledge, attitudes and practices in caregivers of patients with HrCLM by performing focus group discussions (FGDs) with 20 mothers of children with HrCLM in two endemic urban communities in Manaus, Brazil. Additionally, socio-demographic data of 70 actively detected HrCLM patients in both areas were obtained by using questionnaires. Results: We found that mainly children who lived in large households and habitually walked barefoot were affected. Family income was low, housing was poor, and food shortage common. In the FGDs, mothers described HrCLM as a severely distressing condition with considerable impact on individual and family life. Conclusion: Inadequate treatment practices and the identification of poverty-related obstacles for practical prevention of HrCLM by the mothers of affected children indicate that both health education and improvement of living conditions are required jointly.